Fucoidan-Based Nanoparticles with Inherently Therapeutic Efficacy for Cancer Treatment - Chih-Sheng Chiang; Bo-Jie Huang; Jui-Yu Chen; Wee Wei Chieng; Seh Hong Lim; Wei Lee; Weoi-Cherng Shyu; Long-Bin Jeng (MDPI AG, 2021)
The anticancer properties of fucoidan have been widely studied in cancer research. However, the lack of safety information on the parenteral administration of fucoidan and its rapid clearance from the system have limited its application. Herein, we assessed the therapeutic efficacy and safety of fucoidan and developed fucoidan nanoparticles (FuNPs) to enhance their therapeutic effect in the mouse model of breast cancer. FuNPs were synthesized through the emulsion method, and the stable colloid has an average size of 216.3 nm. FuNPs were efficiently internalized into breast cancer cells in vitro, demonstrating an enhanced antitumor activity in comparison with free form fucoidan. After the treatment of FuNPs, the tumor progression was significantly inhibited in viv. The tumor volume was reduced by 2.49-fold compared with the control group. Moreover, the inhibition of the invasion of tumor cells into the lungs revealed the antimetastatic properties of the FuNPs. FuNPs, as naturally marine polysaccharide-based nanoparticles, have shown their broader therapeutic window and enhanced antimetastatic ability, opening an avenue to the development of the inherently therapeutic nanomedicines.